Adapting a humanoid robot for use with children with profound and multiple disabilities - Standen, Penny J.; Brown, David J.; Hedgecock, Joseph; Roscoe, Jess; Galvez Trigo, Maria Jose; Elgajiji, Elmunir (Nova Science, 2016)
With all the developments in information technology (IT) for people with disabilities, few interventions have been designed for people with profound and multiple disabilities as there is little incentive for companies to design and manufacture technology purely for a group of consumers without much buying power. A possible solution is therefore to identify mainstream technology that, with adaptation, could serve the purposes required by those with profound and multiple disabilities. Because of its ability to engage the attention of young children with autism, the role of a humanoid robot was investigated. After viewing a demonstration, teachers of pupils with profound and multiple disabilities described actions they wished the robot to make in order to help nominated pupils to achieve learning objectives. They proposed a much wider range of suggestions for using the robot than it could currently provide. Adaptations they required fell into two groups: either increasing the methods through which the robot could be controlled or increasing the range of behaviours that the robot emitted. These were met in a variety of ways but most would require a degree of programming expertise above that possessed by most schoolteachers.